Pergeseran Makna Sungai Kahayan bagi Masyarakat Dayak Ngaju di Desa Bukit Rawi Kabupaten Pulang Pisau - Wainarisi, Yane Octavia Rismawati; Tumbol, Stynie Nova (Journal of Moral and Civic Education, 2022)
River has many different meaning for people. For Dayak people especially Dayak Ngaju people, river is the center of life. Dayak Ngaju People use river as a central of ritual, social and economic activity moreover they use the name of the river as their identity tribe. But now, people of Dayak Ngaju who live in the borders of rivers only use river for the economic activities and create meaning shift of the rivers itself for them. This research did in people group of Dayak Ngaju Tribe who live in the borders of Kahayan River in Bukit Rawi Village, Pulang Pisau. This people group well known as “Orang Kahayan” than Dayak Ngaju People. The research made by ethnography qualitative method which the data was obtained by literature study, observation, and interview in one month in Bukit Rawi Village. In this research, we meet that is it true if there is a meaning shift of the Kahayan River for local people group in Bukit Rawi, Center Kahayan, Pulang Pisau.